Rutaecarpine inhibits KEAP1-NRF2 interaction to activate NRF2 and ameliorate dextran sulfate sodium-induced colitis - Zhang, Youbo (Free Radic Biol Med, 2019)
Inflammatory bowel disease (IBD) represents a group of chronic relapsing intestinal disorders. Rutaecarpine (RUT), isolated from the Traditional Chinese Medicine (TCM) of Evodia rutaecarpa, was reported to suppress IBD. However, the mechanism by which RUT ameliorates dextran sulfate sodium (DSS)-induced IBD is largely unknown. By use of nuclear factor-erythroid 2–related factor 2 (NRF2) knockout mice, cell-based studies, surface plasmon resonance (SPR), western blotting analysis, and molecular docking studies, the mechanism by which RUT affects DSS-induced colitis was explored. In DSS-treated wild-type mice but not in Nrf2-null mice, RUT significantly improved colitis as revealed by rescued body weight loss, improved histology and inflammation, and induced expression of NRF2 target genes in colon and ileum. Cell-based studies showed that RUT significantly increased the LD(50) for hydrogen peroxide (H(2)O(2))-induced cell damage, activated NRF2 nuclear translocation, and suppressed the production of reactive oxygen species in H(2)O(2)-treated HCT116 cells, activated NRF2 luciferase reporter activities in HCT116 cells and HepG2 cells, and induced expression of NRF2 target genes in primary intestinal epithelial cells. Molecular docking in silico and SPR assays indicated that RUT interacted with kelch-like ECH-associated protein 1 (KEAP1), and extracellular incubation studies revealed that RUT bound to the KEAP1 kelch domain with a calculated equilibrium dissociation constant K(d) of 19.6 μM. In conclusion, these results demonstrate that RUT ameliorates DSS-induced colitis, dependent on NRF2, and could be a potential therapeutic option for IBD patients. Mechanistically, RUT potentiates NRF2 nuclear translocation to upregulate NRF2-mediated antioxidant response by directly inhibiting KEAP1-NRF2 interaction.